Dampak Insentif, Desentraliasi dan Sistim Pengendalian Internal Terhadap Kinerja Pegawai - Rumalatu, Gilbert Alvin; Waelauruw, Anthoneta Telsy (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2021)
Abstract This study aims to test and analyze intensive, decentralization effect and intern government control system to employee performance in Dinas Pariwisata, Pemuda dan Olah Raga Kabupaten Maluku Tengah. Population from the research is from all employees In Dinas Pariwisata, Pemuda dan Olah Raga Kabupaten Maluku Tengah. It takes 46 respondent from the government employees and salaries employees. Data collection is done with a direct survey with census method as a sample gathering method. Hypothesis testing empirically using a Multiple Liniear Regression. The research result shows that intensive is proven positive and significant effect employee performance. This mean if the intensive is raise or getting better have a good effect to employee performances. Decentralization is proven positive and significant to employee performance and this mean that authority delegation and the responsible are not did not go well on employee performance. Further intern control is proven positive and significant effect to employee performance. Which it’s mean if the government control system runs well then it will effect indirectly to employee performance goes better. Keywords ; Intensive, Decentralization, Government Internal Control System, Performance